Isolation and Identification of Hydrocarbon Degrading Bacteria From Used Lubricant Oil - Risa Umami; Dewi Yuliana Rizqi (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2021)
Hydrocarbons are organic compounds consisting of carbon and hydrogen. Petroleum in particulary lubricant oil is a group of hydrocarbon compounds which can be grouped into aliphatic, alicyclic, and aromatic hydrocarbons. The use of oil as a lubricant will leaving used lumbricant oil that if not managed properly will cause environmental pollution. This research aims to isolate and identifying of hydrocarbon degrading bacteria from used lubricant oil. Type of research is descriptve explorative with qualitative approach. Isolation is done by adding the sample of used lubricant oil into the NA medium (Natrient Agar) by observing the clear zone formed. Bacterial identification is done by observing morphology and biochemical activity. Four isolates were obtain and two of them were selected to identification are isolate I and III. The result from bacterial identification was performed based on morphological and biochemical characterization show isolate I is Bacillus brevis and isolate III is Bacillus macerans.